Phương pháp giải:
Để hàm số \(y = \left( {m + 1} \right){x^3} + \left( {m + 1} \right){x^2} - 2x + 2\) nghịch tặc đổi thay bên trên R thì \(y' \le 0\) với \(\forall x \in R\)
Lời giải chi tiết:
Ta có: \(y' = 3\left( {m + 1} \right){x^2} + 2\left( {m + 1} \right)x - 2\).
Để hàm số \(y = \left( {m + 1} \right){x^3} + \left( {m + 1} \right){x^2} - 2x + 2\) nghịch tặc đổi thay bên trên R thì \(y' \le 0\) với \(\forall x \in R\)
suy ra: \(3\left( {m + 1} \right){x^2} + 2\left( {m + 1} \right)x - 2 \le 0\) với \(\forall x \in \mathbb{R}\), \( \Rightarrow \left[ \begin{array}{l}\left\{ \begin{array}{l}a = 0\\bx + c \le 0\end{array} \right.\\\left\{ \begin{array}{l}a \ne 0\\a < 0\\\Delta ' \le 0\end{array} \right.\end{array} \right.\) \( \Rightarrow \left[ \begin{array}{l}\left\{ \begin{array}{l}m = - 1\\ - 2 \le 0{\rm{ }}\left( {l/} \right)\end{array} \right.\\\left\{ \begin{array}{l}m < - 1\\{m^2} + 8m + 7 \le 0\end{array} \right.\end{array} \right.\)\( \Leftrightarrow \left[ \begin{array}{l}m = - 1\\m \in \left[ { - 7;\left. { - 1} \right)} \right.\end{array} \right.\). Theo đầu bài: \(m \in \mathbb{Z}\), \( \Rightarrow m = \left\{ { - 7; - 6; - 5; - 4; - 3; - 2; - 1} \right\}\).
Chọn D.